Choked out: Battling invasive giant cane along the Rio Grande/Bravo Borderlands. (20th September 2021) - Briggs, Mark K.; Poulos, Helen M.; Renfrow, Jeffrey; Ochoa‐Espinoza, Javier; Larson, David; Manning, Patricia; Sirotnak, Joseph; Crawford, Kelon
Abstract: Along the U.S.‐Mexico border, an aggressive non‐native grass, giant cane ( Arundo donax ), grows in dense, nearly impenetrable stands along hundreds of kilometers of the Rio Grande/Bravo (RGB). Between 2008 and 2018, a diverse, multisector binational‐team repeatedly treated giant cane with prescribed fire and herbicide along 90 km of this binational river to restore aquatic and riparian habitat and native plant community composition. The large geographic scale, binational management response, treatment methods used, and development of a long‐term monitoring program to quantify treatment impacts on the RGB's riparian plant community underscore the unique aspects of this effort. Results of this decade‐long management experiment indicate that (i) the combination of a primary treatment of giant cane (using prescribed fire followed 4–6 weeks later by herbicide treatment of regrowth) and a secondary treatment (spot treatment of regrowth one or more years following primary treatment) was effective in reducing the extent and distribution of giant cane at relatively low cost, (ii) giant cane re‐establishment following treatment is often not rapid, nor dramatic; and (iii) as revealed by analysis of riparian vegetation monitoring data, eradication of dense stands of giant cane have fostered significant and long‐term reduction in giant cane cover and recovery of native woody riparian plant taxa. Important caveats to the long‐term viability of managing giant cane hinge on better understanding the consequences of herbicide use, securing funding to cover the cost of re‐treatment, and continuing river flow management focused on promoting the recovery of native riparian obligate plants over non‐natives.